KNOWLEDGE AND BEHAVIOUR REGARDING OSTEOPOROSIS IN WOMEN: Knowledge of Osteoporosis Among Women - Kamran, Muhammad; Iftikhar, Ammara; Awan, Aamir Aslam (Pakistan Armed Forces Medical Journal, 2016)
Objective: To evaluate the knowledge, attitude and practice regarding osteoporosis in women belonging to different educational status Study Design: A cross-sectional descriptive study. Place and Duration of Study: Dist. Hattian Bala of Azad Jammu and Kashmir (AJK) from Oct 2015 to Dec 2015. Material and Methods: A total of 410 women between 12–45 years of age were included in the study and grouped according to educational qualification. Women who were health-care workers, already diagnosed with the disease or those who had never heard of the disease were not included in the study. A self-made, pre-validated questionnaire including demographic data and 24 items assessing knowledge, attitude, and practice (KAP) regarding osteoporosis was administered after obtaining verbal informed consent. The scores ranged from 0-15 in knowledge section, 0-4 in attitude section and 0-8 in practice section. The results in each section of KAP were cross tabulated with educational status of the respondents. Results: Books and teachers (34.60%) were the main source of information followed by television/ radio (22.40%). The mean score for knowledge section was 5.12 ± 1.11, for attitude section 1.65 ± 0.64, and for practice 3.79 ± 2.61. All the three dimensions had significantly better results in women with higher educational status (graduate or more). Conclusion: Women with higher education demonstrated better knowledge, positive attitude and healthier practice than those with lower education.